Sport and social cohesion in a provincial town in South Africa: The case of a tourism project for aid and social development through football - (:unkn) unknown (My University, 2013)
This article examines sport and social cohesion in South Africa through a case study of a project on aid and social development through tourism and football in the provincial town of Stellenbosch, in the Western Cape. The field of study includes the project that was initiated, the group that benefits from it – African footballers – and another group that believes they too were entitled to benefit – Coloured footballers. The observation scale focuses not on the content of the initiative, as the usual sociological approach would do, but on the effects of its allocation. Those effects are observed first from the viewpoint of how they contribute to heighten acceptance of the national governance principles, and then from that of the consequences of that level of acceptance. The results show that the allocation of the project has heightened acceptance of the democratic framework among African footballers, and had the opposite effect among Coloured footballers, who view it as deeply inequitable. In Stellenbosch, the project on aid and social development through tourism and football thus has been harmful to the national project of social cohesion as, far from enhancing the acceptance of the governance framework by all, it has fostered conflict. Next, our results show that allocating the project to one group has strengthened the feeling that there are fundamental differences between the two football groups, by throwing the inequality between them into relief. It has revived among each group the stereotypes inherited from apartheid, in which Coloureds are perceived as ‘racists’ and Africans as ‘primitive’, which harms the South African social cohesion project further, as such stereotypes only contribute to harden the boundaries between the different groups.
Keywords: African Research